Energy performance of sugarcane harvesters equipped with knives and saws for basal cutting - Marques Filho, Aldir C.; Testa, João V. P.; Martins, Murilo B.; Bortolheiro, Fernanda P. de A. P.; de Almeida, Pablo L.; Lanças, Kléber P. [UNESP] (FapUNIFESP (SciELO), 2025)
The mechanized cutting of sugarcane requires improvements, as cutting tools can affect the longevity of sugarcane fields and increase production costs. Furthermore, these tools can increase the energy demand of machines in the field. This study evaluated the sugarcane harvester performance equipped with different basal cutting devices: impact cutting (blades) and continuous cutting (saws) in three commercial sugarcane production areas. The experimental design was completely randomized in a 3 × 2 factorial scheme with six repetitions. Effective fuel consumption and harvesting capacity were evaluated. The saws increased fuel consumption per area by 3.9 and 8.9% per Mg harvested. The crop’s yield characteristics determine harvesting systems’ energy demand. For yields above 90 Mg ha-1, energy demand has stabilized up to 120 Mg ha-1. The fuel demand for harvesting ranged between 1.0 and 1.2 L Mg-1 of harvested material. Regardless of the cutting system, each Mg requires 37.3 kJ of energy to be removed from the field.
Desempenho energético de colhedora de cana-de-açúcar equipada com facas e serras para corte basal
Keywords: energy demand; mechanization; operational efficiency; Saccharum officinarum; sustainability